Spatial Development and Agglomeration Economies in Services--Lessons from India - Ghani, Ejaz; Goswami, Arti Grover; Kerr, William R. (World Bank, Washington, DC, 2016)
Although many studies consider the spatial pattern of manufacturing plants in developing countries, the role of services as a driver of urbanization and structural transformation is still not well understood. Using establishment level data from India, this paper helps narrow this gap by comparing and contrasting the spatial development of services with that in manufacturing. The study during the 2001-2010 period suggests that (i) services are more urbanized than manufacturing and are moving toward the urban and, by contrast, the organized manufacturing sector is moving away from urban cores to the rural periphery; (ii) manufacturing and services activities are highly correlated in spatial terms and exhibit a high degree of concentration in just a few states and industries; (iii) manufacturing in urban districts has a stronger tendency to locate closer to larger cities relative to services activity; (iv) infrastructure has a significant effect on manufacturing output, while human capital matters more for services activity; and lastly, (v) technology penetration, measured by the penetration of the Internet, is more strongly associated with services than manufacturing. Similar results hold when growth in activity is measured over the study period rather than levels. Manufacturing and services do not appear to crowd each other out of local areas.